Language teachers' narratives of practice - Moloney, Robyn (Cambridge Scholars Publishing, 2013)
Language Teachers' Narratives of Practice is a collection of seventeen essays that examine personal and professional stories of, and by, language teachers in diverse Australian contexts. The voices of twenty-one Australian language teachers in all, describe teachers' own linguistic and cultural, personal and professional narratives, and how each narrative has informed the construction of their classroom language teaching practice to suit their teaching contexts. We see how teachers make individual responses to emerging pedagogies, developed through the lens of their personal experience and understanding of language and culture. In our invitations to these teachers to contribute chapters to the book, we have encouraged them to make visible the diversity within the Australian language teaching context. This is a new resource for use in a professional development context, for pre-service teachers, in-service teachers, tertiary teacher educators and researchers. This resource will serve as a practical text for teachers to draw on, to extend their own professional knowledge and classroom practice in relevant, useful and diverse areas. The narratives can be examined as case studies of teacher identity and life-worlds, development of pedagogies, intercultural learning, and the differentiation and adaptation needed in particular environments, within a diverse environment such as Australia.